THE IMPORTANCE OF CONSIDERING THE CULTURAL CONTEXT : WHEN EVALUATING L’NU CHILDREN’S EARLY YEARS DEVELOPMENT OUTCOMES (Canadian Journal of Native Studies, 2026)
L’nu (Mi’kmaw) children’s cultural education is often merged with or overridden by westernized methods of teaching,learning, and assessment in Canada’s school systems. An Etuaptmumk/ Two-Eyed Seeing (E/TES) approach from an Indigenous,and in particular a Mi’kmaq, worldview honours traditional knowledge and teaching while recognizing that we work and learn in systems that originate from westernized points of view. E/TES allows alternate ways of knowing and being in the world through a co-learning process that brings Indigenous worldview and western perspectives together. The education and health outcomes of L’nu children are often not on par with those of non-L’nu children, perhaps suggesting that westernized assessments inaccurately capture education and health markers without cultural context. From the view of two L’nu educators, this paper aims to shed light on the experiences of L’nu children as they enter the education system in their early years and offers a differing perspective for viewingdevelopment, school readiness, and assessment.